2019
DOI: 10.1161/str.50.suppl_1.wp203
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP203: Frequency of Post-stroke Depression Among Hypertensive Black and Hispanic Stroke Survivors

Abstract: Introduction: Post-stroke depression (PSD) is estimated to affect one-third of stroke survivors and is associated with long-term disability but scarce data exist in minority populations. This analysis examined the frequency and correlates of PSD in a cohort of Black and Hispanic stroke survivors. Methods: We analyzed baseline data from an ongoing clinical trial comprising 450 Blacks and Hispanics with recent stroke from New York City stroke centers. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There was no significant difference between intervention groups for non-Hispanic White patients in the study, and no analysis comparing effects by race was reported. The only other available evidence related to health disparities was reported by researchers at NYU Grossman School of Medicine, 71 who presented a novel study (not yet published) of Black and Hispanic stroke survivors with uncontrolled blood pressure at the International Stroke Conference 2020. The study found that patients who received home blood pressure monitoring plus telephone-based lifestyle counseling by nurses had greater reductions in SBP than patients who participated only in home blood pressure monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between intervention groups for non-Hispanic White patients in the study, and no analysis comparing effects by race was reported. The only other available evidence related to health disparities was reported by researchers at NYU Grossman School of Medicine, 71 who presented a novel study (not yet published) of Black and Hispanic stroke survivors with uncontrolled blood pressure at the International Stroke Conference 2020. The study found that patients who received home blood pressure monitoring plus telephone-based lifestyle counseling by nurses had greater reductions in SBP than patients who participated only in home blood pressure monitoring.…”
Section: Discussionmentioning
confidence: 99%